Economic Community of West African States (ECOWAS) regional action plan for rice self-sufficiency by 2025 - CGIAR Research Program on Rice (2020)
The ECOWAS Region rice offensive was approved by the ECOWAS Council of Ministers in June 2014. This Offensive aims to reduce imports to zero by 2025, and increase trade intégration.